Time-domain poroelastic full-waveform inversion of shallow seismic data: methodology and sensitivity analysis - Liu, Tingting; Bohlen, Thomas (Geophysical Journal International, 2022)
Full-waveform inversion (FWI) is considered as a high-resolution imaging technique to recover the geophysical parameters of the elastic subsurface from the entire content of the seismic signals. However, the subsurface material properties are less well estimated with elastic constraints, especially for the near-surface structure, which usually contains fluid contents. Since Biot theory has provided a framework to describe seismic wave propagations in the poroelastic media, in this work, we propose an algorithm for the 2-D time-domain (TD) poroelastic FWI (PFWI) when the fluid-saturated poroelastic equations are applied to carve the physical mechanism in the shallow subsurface. To detect the contribution of the poroelastic parameters to shallow seismic wavefields, the scattered P-SV&SH wavefields corresponding to a single model parameter are derived explicitly by Born approximation and shown numerically afterward. The Fréchet kernels are also derived and exhibited in P-SV&SH schemes to analyse the sensitivities of the objective function to different poroelastic parameters. Furthermore, we verify the accuracy of the derivations through model parameter reconstructions. We perform a series of numerical tests on gradients with respect to different model parameters to further evaluate inter-parameter trade-offs. PFWI holds potential possibilities to directly invert fluid-related physical parameters of the shallow subsurface.